Effect of Sub-energy Windows’ Parameters on the Triple Energy Window Scatter Correction Method Accuracy in 99mTc SPECT Imaging - H. Saikouk; N. E. Khayati; A. Matrane (PPIKSN-BATAN, 2022)
Scatter correction in SPECT quantification is of major importance to compensation for the scatter contribution under the photopeak. The triple energy windows method (TEW) is one of the suggested ways for scatter correction that are widely used in clinical routine. However, it can be a source of additional noise if the width or the number of sub-energy windows is not accurately chosen. To determine the precise scatter estimation windows settings under the 99mTc photopeak, scatter fraction was calculated for different sub-energy widths and numbers through GATE Monte Carlo simulation, for a main energy window of 15 %, centered at 140 keV. Four different acquisitions, with cold or hot inserts in a warm or a cold background, were studied. The estimation was done by two methods. The first method was the extraction of the number of detected Compton photons under the photopeak, therefore considered as the true scattered photons. The second method was the application of TEW method to the simulated energy spectra. The comparison of results corresponding to both methods shows a good agreement in two cases: simultaneous 7 % and 5 % sub-energy windows, respectively, positioned on the left and the right of the main energy window, and the second case is a 3 % left sub-energy window without a right sub-energy window. These sub-energy windows were then applied to experimental tomographic acquisitions to assess their impact on contrast, relative noise of the background (RNB), signal‑to‑noise ratio (SNR), integral uniformity (IU), and tomographic spatial resolution. Good results for these quantitative parameters were acquired with simultaneous 7 % and 5 % sub-energy windows. However, there was very little enhancement for tomographic spatial resolution.